Methodological basis of the system analysis of industrial enterprises’ economic stability - Кравченко, Марина Олегівна (Technology audit and production reserves, 2016)
Feasibility of applied system analysis for the research of the enterprises from the standpoint of system-structural paradigm for solving the problem of ensuring their economic sustainability is proved in the article. This is due to the relevance and unsolving of the problem of providing enterprises’ economic stability during a recession, on the one hand, and the lack and the need of methodological support for the formation of a new paradigm on the other hand. Critical analysis of the main provisions of system-structural paradigm allows assimilating the methodological principles of the new approach to the methodology of general systems theory, which was carried out in the article. As a result of the research procedures have been adapted for applied system analysis, and adjusted its typical sequence taking into account the lack of empirical data, creating rules for its application within the new system-structural paradigm. This allowed to carry out the identification of the enterprise as tetrad consisting of four types of subsystems that differing by the nature of space-time restrictions and the matrix structure of his inner circle, and to determine the mechanism of formation of economic stability. As a result, it was determined eight groups of parameters that are useful for econometric modeling, and made the selection of statistical indicators for their evaluation according to domestic machine-building enterprises. Results of the study can be used by economists, the scope of scientific interest of which includes issues of ensuring economic stability, and the followers of the new system-structural paradigm for the empirical study of its provisions.